Life-course social and economic circumstances, gender, and resilience in older adults: The longitudinal International Mobility in Aging Study (IMIAS). (December 2016) - Phillips, Susan P.; Auais, Mohammad; Belanger, Emmanuelle; Alvarado, Beatriz; Zunzunegui, Maria-Vitoria
Abstract: Although early socioeconomic adversity is associated with poorer function and health in adulthood, those who are able to adapt positively to such risks and threats develop a resilience that may ameliorate harm. Predictors of resilience have been examined in children, however exploring the relationship between life-course events, lived environments and current resilience among older adults across countries is novel. We specifically studied how childhood social and/or economic adversity and current socioeconomic resources were associated with resilience in 2000 community dwelling older men and women in Canada, Colombia, Brazil and Albania. The longitudinal International Mobility in Aging Study (IMIAS) collected information in 2012 and 2014 on childhood adversity, current income sufficiency social support and social engagement, and resilience (Wagnild Resilience Scale RS-14). Resilience levels were moderately high, and similar among women and men. Early social adversity predicted later resilience for some, with women but not men adapting positively. In contrast there was no bouncing back from early economic adversity. Current social engagement aligned with resilience (women only) as did social support from children (for women) and friends (for men). Partner support was of no advantage to either. Among men economic circumstances were stronger correlates of resilience while for women social circumstances were primary. The impact of site on resilience suggested that cultural norms and values have an independent effect on resilience of their populations, with strong and positive social ties more typical of Latin America than Canada appearing to offset lower absolute incomes. These findings are of importance because resilience is dynamic, can be fostered across the lifespan and is generally associated with greater health. Understanding which social assets and resources can be reinforced to build individual resilience offers a means for decreasing the harms of social and economic adversity. Highlights: Resilience in older adults seems gendered and linked to cultural norms and resources. Early social adversity predicts later resilience in women but not men. The harm of early economic deprivation is lifelong, particularly for men. Resilience is greatest among men with friends and women with supportive families. Cohesive social environments may augment resilience despite lower economic status.